Determination of Coagulant Dosage and Stirring Time in Laboratory Wastewater Pretreatment - Maria Siswi Wijayanti; Tuty Emilia Agustina; Muhammad Hatta Dahlan; Dedi Teguh (Research Centre of Inorganic Materials and Complexs, 2022)
The use of chemicals in practical activities or research in the laboratory will certainly produce wastewater. Wastewater generated from the laboratory is classified as hazardous and/or toxic waste. Based on the substances contained in laboratory wastewater in terms of accumulated amount and a long period of time, wastewater will pollute the environment and will have an impact on living things around it if it is directly discharged into water bodies. The composition of laboratory waste is reactive and dangerous because it contains heavy metals Pb, Fe, and Cu as well as high Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) so it is difficult to decompose in nature. This study aimed to prepare the laboratory wastewater using the coagulation process as pretreatment. Therefore, this research prioritized the reduction of heavy metal levels of Pb, Fe, and Cu and reduced the content of COD and TSS with Alum as a coagulant. The highest degradation percentage of COD and TSS content occurred at the Coagulation Dose of 80 ppm, namely 99.79% and 99.80% respectively. Meanwhile, the highest degradation percentage of heavy metal levels of Pb, Fe, and Cu as well as the optimum COD and TSS content occurred at a stirring time of 60 minutes respectively, which were 49.48%, 58.96%, 94.09%, 99.97%, and 99.40%. It was concluded that the pretreatment of laboratory wastewater using the coagulation process could reduce the levels of Pb, Fe, and Cu metals, and the content of COD and TSS.